The cytotoxic effects a of ACA1 on human melanoma cell line - R. Yaraie; M.R. Jalali Nadoushan; M. Naseri; S. Shahrokhi; T. Ghazanfari; M. Kardar (Journal of Mazandaran University of Medical Sciences, 2006)
Background and purpose: Different methods such as surgery, chemotherapy, radiotherapy, hormone therapy and immunotherapy are used for treatment of melanoma cancer. Unfortunately they don't always have desirable results and they may have unfavorable side effects. Researchers try to find new, more effective drugs with low side effects. In this study we evaluated the cytotoxic effect of ACA-1, a water extract of a traditional Iranian medicinal herbs on a melanoma cell line SKMEL-3.Materials and Methods: The SKMEL3 cell line was obtained from Pasture institute, Tehran, Iran and cultured in RPMI media supplemented with 10% FBS. Equal number of cells were added to a 96 well microplate and were incubated with various doses of ACA1 (5,2,1,0.2,0.1,0.05,0.02 and 0.01 mg/ml) for 24, 48 and 72 hours in parallel. The cytotoxic effects of the drug was evaluated using MTT assay.Results: The Results showed that ACA1 has significant cytotoxic effects with dose and time dependent manner on SKMEL3. The optimum dose (5 mg/ml) showed 47% cytotoxicity in 24 h, 65% cytotoxicity in 48 h and 71% cytotoxicity in 72 h. Conclusion: Based on the results of this research, ACA1 is a suitable candidate for chemotherapy of melanoma patients. Further studies are necessary in order to find effective drugs, their effects on other cell lines and approved in vivo models and clinical trials.